2009
DOI: 10.1007/s00467-009-1269-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of certain constituents of antioxidant defense in youth treated in the past for steroid-sensitive idiopathic nephrotic syndrome

Abstract: Disorders of lipid metabolism and antioxidant defense capacity reported during idiopathic nephrotic syndrome (INS) exacerbations are known. The aim of this study was to evaluate constituents of antioxidant defense [total antioxidant potential: ferric-reducing antioxidant power (FRAP), paraoxonase-1 (PON-1), tocopherols, ascorbic acid] in patients formerly treated for INS. The studied group consisted of 30 patients (20 males and 10 females) treated 4-15 years ago for INS. The control group consisted of 30 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A study by Mishra et al 28 showed no complete normalization of plasma levels of MDA after 6 months of induction of INS remission. Another study by Kniazewska et al 29 showed complete normalization of serum levels of ferric-reducing antioxidant power and paraoxonase-1 after 4-15 years of induction of INS remission, regrettably, MDA was not tested in this study. Nevertheless, our findings still have important clinical implications that the therapy of antioxidants should be used in both the active and remission stage of INS.…”
Section: Discussionmentioning
confidence: 61%
“…A study by Mishra et al 28 showed no complete normalization of plasma levels of MDA after 6 months of induction of INS remission. Another study by Kniazewska et al 29 showed complete normalization of serum levels of ferric-reducing antioxidant power and paraoxonase-1 after 4-15 years of induction of INS remission, regrettably, MDA was not tested in this study. Nevertheless, our findings still have important clinical implications that the therapy of antioxidants should be used in both the active and remission stage of INS.…”
Section: Discussionmentioning
confidence: 61%
“…Kniazewska et al (15) have investigated TAC, PON-1, α-tocopherols, ascorbic acid in patients who had been treated 4-15 years ago and healthy subjects. They found no statistically significant differences in PON-1 activity, α-tocopherol levels and the sum of β- and γ-tocopherols and TAC between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with idiopathic NS with severe proteinuria have lipid metabolic disorders and face an increased risk of thromboembolism . Dyslipidaemia in NS may lead to endothelial dysfunction and a risk for atherosclerosis in adults, as well as myocardial infarction and stroke …”
Section: Cardiovascular and Endocrinologic Complicationsmentioning
confidence: 99%